Contribuições das diferentes propostas de alfabetização para a ação pedagógica na escola pública - Lima, Vanessa Bispo (2015)
This document presents a study about the different proposals of literacy and their contributions to the pedagogical action developed in the classroom by literacy teachers. The aim is to investigate the different formations for literacy teachers on public schools. From a methodological point of view, the present work was developed according to the methodology of non-directive perspective of qualitative research. The research study looks at how knowledge about literacy proposals helps the teachers to practice it. The current situation of literacy methods in education, built from numerous scientific data created the idea of magic solutions, as if this or that method was the revolutionary solution that lacked on literacy. In this context, it's necessary an analysis of the ideas brought by literacy methods an d how this contribute to the school literacy teachers practice , showing us an issue that goes much further, demanding an open epistemological posture, to see, and not to accept dichotomies that divide the field between right and wrong